Can the resurrection of the dead preserve personal identity? - Romerales Espinosa, Enrique (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
The belief in the resurrection of the dead is a central tenet for the Abrahamic religions. Given the current discredit of the notion of soul, many materialist Christian philosophers reconsider the possibility of resurrection. Two basic problems loom over this possibility: spatio-temporal discontinuity between death and resurrection (which would preclude resurrection if intermittent existence were impossible for human beings) and degeneration, disaggregation or even complete destruction of the material components of the body (which would prevent the reconstitution of the original body). Both issues endanger numerical identity between the dead and the resurrected person. After surveying various recent hypotheses aimed at overcoming these difficulties, I verify that these theories either resource to farfetched ideas to secure identity, or they directly concede that the resurrected body is a mere copy of the original one. Thus, I conclude that, under a purely corporeal conception of person, no notion of resurrection that preserves personal identity seems feasible.